An Analysis of Language Styles Used by Taylor Swift in Her Iheartradio Speech as The Winner of The Innovator Award - Eris Sasqia Mei Liana; Syafrizal; Fargianti, Yusti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The objective of the research was to determine the types of the language styles used by Taylor Swift in Her iHeartRadio Speech as the Winner of the Innovator Award. This research identifies the most dominant type of language styles used by Taylor Swift in Her iHeartRadio Speech as the Winner of the Innovator Award. This research also aims to determine the theory of social factors according to Janet Holmes (2013) which influences the use of language style. The method used in this thesis is a qualitative method. The research design in this research is content analysis. The data source is video from official Youtube IheartRadio. The dominant type of language style is consultative style. The researcher found that there were 7 of Consultative Style, 5 of Casual Style, 2 of Formal Style, 1 of Intimate Style, and 0 data of Frozen Style. There are some factors that influence the choice of language style, they are participant, setting, topic, and function. Taylor Swift’s speech at the iHeartRadio Awards shows how using different language styles can make communication more effective and this is also useful in education field. The language style that Taylor Swift uses in her speech can be used in the field of education. Using the appropriate language style at the right moment can significantly enhance the effectiveness of communication.